Can higher education policy boost intergenerational mobility? Evidence from an empirical matching model - Jack Britton; Mónica Costa Dias; David Goll (Institute for Fiscal Studies (IFS), 2023)
Higher education policy potentially has an important role in improving intergenerational income mobility. We use rich administrative data to estimate a novel two-sided matching model of sorting into field and institution within higher education. We use it to simulate a wide set of policies aimed at boosting mobility. We find that substantially improving population-level mobility statistics with higher education policy is very difficult. However, there is considerable scope to narrow gaps in outcomes between richer and poorer students who leave school with good attainment levels. From a set of policies aimed at influencing student demand, we conclude that by far the most effective policies would target what people study, rather than whether or where they study. However, the biggest improvements in terms of mobility come from an aggressive policy that targets the supply side by enforcing universities to give preferential admission to poorer students who graduate near the top of their secondary school class. This policy would substantially narrow earnings gaps between richer and poorer students with good prior attainment, without significant costs to the taxpayer.
Keywords: I23; I24; I26; 330; Higher education choices; tuition fees